Effects of hemp seed and flaxseed on enzyme activity in the broiler chicken digestive tract - Taubner, T; Skřivan, M; Englmaierová, M; Malá, L (Animal, 2023)
The activity of enzymes in the digestive tract is an important parameter for appropriate digestive tract function. Feed mixtures can be adjusted to support enzymatic activity in different parts of the digestive tract. Flaxseed and hemp seed are commodities and significant sources of nutrition, and their addition to feed could change enzymatic activity in the digestive tract and improve nutritional intake. The aim of this study was to determine the effects of flaxseed, hemp seed and a combination of both on basic enzymes in the polysaccharidase group, such as amylase, cellulase, pectinase, xylanase and inulinase; basic enzymes in the disaccharidase group, including maltase, invertase and lactase; proteinases and lipases in the digestive tract of broiler chickens. During the experiment, the control group was fed a diet without flaxseed or hemp seed. The diet of the second group contained 80 g/kg flaxseed, the diet of the third group contained 40 g/kg hemp seed, and the diets of the fourth to sixth groups contained 80 and 30 g/kg, 80 and 40 g/kg and 80 and 50 g/kg flaxseed and hemp seed, respectively. Enzyme activity was found to depend on the location in the digestive tract and the composition of the feed mixture (P < 0.05). Most enzymatic conversion occurs in the ileum, where the addition of flaxseed and hemp seed to the diet increased most enzyme activities, namely, amylase, cellulase, pectinase, xylanase, maltase, invertase, proteinase and lipase activities. The highest values of enzyme activity were found in groups IV-VI fed a combination of flaxseed and hempseed, especially in chickens fed diet VI (flaxseed and hemp seed at 80 and 50 g/kg). Growth performance results confirmed the enzyme activity results, as the weights of the chickens increased after the addition of flaxseed and/or hemp seed. The findings have economic implications, suggesting that feeding a diet with a combination of flaxseed and hemp seed is beneficial.
Keywords: kur domácí; Animal Nutritional Physiological Phenomena; fyziologie výživy zvířat; beta-Fructofuranosidase; Enzymes; Animal Feed; Chickens; polygalakturonasa; Gastrointestinal Tract; Hemp; alfa-glukosidasy; krmivo pro zvířata; len; amylasy; potravní doplňky; dieta; Dietary Supplements; Nutrition; alpha-Glucosidases; Cellulases; Poultry; Animals; Amylases; Polygalacturonase; zvířata; celulasy; Diet; gastrointestinální trakt; Cannabis; Flax; invertasa